Feasibility and Usability Pilot Study of a Novel Irritable Bowel Syndrome Food and Gastrointestinal Symptom Journal Smartphone App. Issue 3 (March 2016) - Zia, Jasmine; Schroeder, Jessica; Munson, Sean; Fogarty, James; Nguyen, Linda; Barney, Pamela; Heitkemper, Margaret; Ladabaum, Uri
Abstract : OBJECTIVES: : Seventy percent of patients with irritable bowel syndrome (IBS) identify certain foods as triggers for their symptom flare‐ups. To help identify potential trigger foods, practitioners often rely on patient food and gastrointestinal (GI) symptom journaling. The aim of the study was to evaluate the feasibility and usability of a novel food and symptom journal app, specifically designed for patients with IBS. Secondary aims were to explore the effect of using the app on GI symptoms and to describe associations between diet and GI symptoms suggested by individual patient data. METHODS: : The feasibility and usability of the novel app was studied in 11 IBS patients (8 women), aged 21–65 years. Participants were asked to log GI symptoms (abdominal pain, bloating, diarrhea, constipation) using a 100‐point color‐graded sliding scale (green=none, red=severe) four times a day and to log every meal/snack they ate (at least three times a day) over a 2‐week period. The app's feasibility as a data collection tool was evaluated by daily completion, compliance, data hoarding, and fatigability rates. Usability was evaluated with the System Usability Scale (SUS). To explore potential impact of using the app on bowel distress, we compared before and after intervention IBS‐Symptom Severity Scale (IBS‐SSS) scores. Meal entries were analyzed for nutrients using the Nutrition Data System for Research. Regression analyses were conducted for each participant journal to explore relationships between meal nutrients and subsequent GI symptoms. RESULTS: : Daily average completion rates of the minimum requested entries for meal and GI symptoms were 112±47% and 78±44%, respectively. Average 24‐h compliance rates were 90±19% and 94±12%, respectively. The SUS score was above average (mean 83, range 65–97.5; n =10). Most participants did not have a clinically significant decrease in IBS‐SSS. At least one strong association ( P ≤0.05) between GI symptoms and a meal nutrient was found in 73% of participants. The mean number of associations was 2 (range 0–7; n =11). Patterns of associations differed between individual participants. CONCLUSIONS: : Our app appeared to be a feasible and usable tool for IBS patients. Our findings are in line with anecdotes that most IBS patients have food triggers and that these vary by individual. Future studies can explore whether individualized dietary changes guided by an app can result in IBS symptom improvement.